2020
DOI: 10.1111/jebm.12382
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance of systematic reviews as Master/PhD theses in Brazilian graduate programs in dentistry

Abstract: Objective: This study aimed to evaluate whether a master and PhD thesis in Brazilian graduate programs in dentistry can be based on a systematic review (SR). Methods:In this cross-sectional study, we surveyed the coordinators of Brazilian graduate programs in dentistry using a self-administered questionnaire including questions about whether an SR meets requirements for approval of a master or PhD thesis, instructions regarding how to use an SR as the method for a master or PhD thesis, and reasons and barriers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…A significant number of systematic review abstracts (n=235) were presented in the SBPqO meeting since establishing a special section for this type of study. Three aspects could be involved in this result: 1) Bassani et al (2019) 3 demonstrated that Brazil is one of the countries that publish the most systematic reviews in dentistry; 2) Dotto et al (2020) 18 showed that systematic reviews are well accepted as a Master's or PhD thesis by Brazilian graduate programs in dentistry; and 3) Brazil has an upper-middle-income economy and systematic reviews are cheaper than other methodologies such as randomized controlled trials resulting in a research methodology appropriate for this setting 18 .…”
Section: Discussionmentioning
confidence: 99%
“…A significant number of systematic review abstracts (n=235) were presented in the SBPqO meeting since establishing a special section for this type of study. Three aspects could be involved in this result: 1) Bassani et al (2019) 3 demonstrated that Brazil is one of the countries that publish the most systematic reviews in dentistry; 2) Dotto et al (2020) 18 showed that systematic reviews are well accepted as a Master's or PhD thesis by Brazilian graduate programs in dentistry; and 3) Brazil has an upper-middle-income economy and systematic reviews are cheaper than other methodologies such as randomized controlled trials resulting in a research methodology appropriate for this setting 18 .…”
Section: Discussionmentioning
confidence: 99%